Design of Experiment (DoE) Approach for Developing Inhalable PLGA Microparticles Loaded with Clofazimine for Tuberculosis Treatment - Druva Sarika Rongala; Suyash M. Patil; Nitesh K. Kunda (MDPI AG, 2024)
Tuberculosis (TB) is an airborne bacterial infection caused by Mycobacterium tuberculosis (M. tb), resulting in approximately 1.3 million deaths in 2022 worldwide. Oral therapy with anti-TB drugs often fails to achieve therapeutic concentrations at the primary infection site (lungs). In this study, we developed a dry powder inhalable formulation (DPI) of clofazimine (CFZ) to provide localized drug delivery and minimize systemic adverse effects. Poly (lactic acid-co-glycolic acid) (PLGA) microparticles (MPs) containing CFZ were developed through a single emulsion solvent evaporation technique. Clofazimine microparticles (CFZ MPs) displayed entrapment efficiency and drug loading of 66.40 ± 2.22 %w/w and 33.06 ± 1.45 µg/mg, respectively. To facilitate pulmonary administration, MPs suspension was spray-dried to yield a dry powder formulation (CFZ SD MPs). Spray drying had no influence on particle size (~1 µm), zeta potential (−31.42 mV), and entrapment efficiency. Solid state analysis (PXRD and DSC) of CFZ SD MPs studies demonstrated encapsulation of the drug in the polymer. The drug release studies showed a sustained drug release. The optimized formulation exhibited excellent aerosolization properties, suggesting effective deposition in the deeper lung region. The in vitro antibacterial studies against H37Ra revealed improved (eight-fold) efficacy of spray-dried formulation in comparison to free drug. Hence, clofazimine dry powder formulation presents immense potential for the treatment of tuberculosis with localized pulmonary delivery and improved patient compliance.